Finite-Time Stability and Control - Amato, Francesco; Ambrosino, Roberto; Ariola, Marco; Cosentino, Carlo; De Tommasi, Gianmaria (Lecture Notes in Control and Information Sciences, 2014)
Finite-time stability (FTS) is a more practical concept than classical Lyapunov stability, useful for checking whether the state trajectories of a system remain within pre-specified bounds over a finite time interval. In a linear systems framework, FTS problems can be cast as convex optimization problems and solved by the use of effective off-the-shelf computational tools such as LMI solvers. Finite-time Stability and Control exploits this benefit to present the practical applications of FTS and finite-time control-theoretical results to various engineering fields. The text is divided into two parts: ·         linear systems; and ·         hybrid systems. The building of practical motivating examples helps the reader to understand the methods presented. Finite-time Stability and Control is addressed to academic researchers and to engineers working in the field of robust process control. Instructors teaching graduate courses in advanced control will also find parts of this book useful for their courses.